Prenatal vitamin D and cord blood insulin-like growth factors in Dhaka, Bangladesh. Issue 6 (June 2019) - Bilic, Monika; Qamar, Huma; Onoyovwi, Akpevwe; Korsiak, Jill; Papp, Eszter; Al Mahmud, Abdullah; Weksberg, Rosanna; Gernand, Alison D; Harrington, Jennifer; Roth, Daniel E
Abstract : Fetal growth restriction is linked to adverse health outcomes and is prevalent in low- and middle-income countries; however, determinants of fetal growth are still poorly understood. The objectives were to determine the effect of prenatal vitamin D supplementation on the insulin-like growth factor (IGF) axis at birth, to compare the concentrations of IGF-I in newborns in Bangladesh to a European reference population and to estimate the associations between IGF protein concentrations and birth size. In a randomized controlled trial in Dhaka, Bangladesh, pregnant women enrolled at 17–24 weeks of gestation were assigned to weekly oral vitamin D3 supplementation from enrolment to delivery at doses of 4200 IU/week, 16, 800 IU/week, 28, 000 IU/week or placebo. In this sub-study, 559 woman–infant pairs were included for analysis and cord blood IGF protein concentrations were quantified at birth. There were no significant effects of vitamin D supplementation on cord blood concentrations of IGF-I ( P  = 0.398), IGF-II ( P  = 0.525), binding proteins (BPs) IGFBP-1 ( P  = 0.170), IGFBP-3 ( P  = 0.203) or the molar ratio of IGF-I/IGFBP-3 ( P  = 0.941). In comparison to a European reference population, 6% of girls and 23% of boys had IGF-I concentrations below the 2.5th percentile of the reference population. IGF-I, IGF-II, IGFBP-3 and the IGF-I/IGFBP-3 ratio were positively associated with at least one anthropometric parameter, whereas IGFBP-1 was negatively associated with birth anthropometry. In conclusion, prenatal vitamin D supplementation does not alter or enhance fetal IGF pathways.